Palonosetrona versus ondansetrona para profilaxia de náuseas e vômitos pós-operatórios em colecistectomias videolaparoscópicas. Estudo controlado randomizado de não-inferioridade - Davolos, Francisco José Chiaradia (2020)
Nausea and vomiting are one of the most common postoperative complications, reaching 80% of patients with associated risk factors. Recently, palonosetron, an antiemetic antagonist of 5-HT3 serotonin receptors, has been used as prophylaxis for this complication. In the present randomized controlled noninferiority trial, it is tested the hypothesis that palonosetron is non-inferior to ondansetron within the margin of 15% of risk difference, at reducing the incidence of postoperative nausea and vomiting in videolaparoscopic cholescystectomy. Two hundred and twelve patients of both sexes who underwent videolaparoscopic cholescystectomy with general anesthesia were selected and double-blind and randomly assigned into two groups which received intravenous palonosetron, 0.075 mg, or intravenous ondansetron, 8 mg, before the induction. The same dose of ondansetron was administered eight and sixteen hours after surgery. Anesthesia and surgery were standardized for all patients. Nausea and vomiting were evaluated during 24 hours after surgery. The highest incidence of nausea and vomiting occurred between 2 and 6 hours postoperative, being values in percent (95% confidence interval (CI)) of 36.8 (28.2 - 46.3) and 43.4 (34.4 – 52.9) in palonosetron and ondansetrona groups, respectively. The risk difference (95% CI) between palonosetron and ondansetron for nausea and vomiting was 0 (-10.9 to 10.9), -6.6 (-19.4 to 6.5), -0.9 (-11.0 to 9.2) and -2.8 (-9.6 to 3.6) in the postoperative time intervals between 0 to 2 hours, > 2 to 6 hours, > 6 to 12 hours and > 12 to 24 hours, respectively. There was no difference between the groups in rescue drug administration (dimenhydrinate) and there were no adverse events associated with the study drug. We conclude that palonosetron has a non-inferior effect to ondansetron when used in patients at risk for postoperative nausea and vomiting undergoing videolaparoscopic cholecystectomy, being a good option for prophylaxis of nausea and vomiting, as it is administered in a single dose.